2022
DOI: 10.1055/s-0041-1741400
|View full text |Cite
|
Sign up to set email alerts
|

Quality-Based Evaluation of Patient-Facing Online Education Materials Regarding Facial Filler Procedures

Abstract: Injectable facial fillers have become tremendously more popular in recent years, and the Internet offers a proportional amount of consumer-facing educational material. This study sought to explore the quality of these online materials. The top 20 Web sites offering educational materials about facial filler were identified via Google search and sorted by source: Medical Professional Boards, Hospitals and Providers, Medical News and Reference, and Fashion. The materials were assessed for overall quality with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“… 1 , 2 , 11 However, not as many have directly analyzed the accuracy of web-based materials by website source type. In a few studies that did, the advisability rate ranged from 49.4%, as reported by Peterson et al 20 in their analysis of 87 webpages for the quality of musculoskeletal information on the Internet, to between 76% and 99%, as in Beer et al’s 6 investigation of information regarding facial filler procedures. Our prior analysis of 99 websites regarding pitching recommendations in baseball yielded an advisability rate of 76.8%.…”
Section: Discussionmentioning
confidence: 88%
“… 1 , 2 , 11 However, not as many have directly analyzed the accuracy of web-based materials by website source type. In a few studies that did, the advisability rate ranged from 49.4%, as reported by Peterson et al 20 in their analysis of 87 webpages for the quality of musculoskeletal information on the Internet, to between 76% and 99%, as in Beer et al’s 6 investigation of information regarding facial filler procedures. Our prior analysis of 99 websites regarding pitching recommendations in baseball yielded an advisability rate of 76.8%.…”
Section: Discussionmentioning
confidence: 88%
“…12 Information regarding cosmetic injectables is no exception to this trend. In an evaluation of online patient education materials regarding facial filler procedures, Beer et al 14 found that educational materials related to injectable facial fillers are of subpar quality, with 15% failing to mention any risks or adverse effects. Although patients may look toward online sources to obtain health information, the burden of obtaining informed consent ultimately falls to the responsible provider.…”
Section: Discussionmentioning
confidence: 99%